Development of Genially Based Interactive Learning Multimedia for Social Studies (IPS) in Grade VII at SMP Negeri 32 OKU - Aziza Sri Wahyuni; Yamanto Isa; Leni Pebriantika (Sakura Digital Nusantara, 2026)
This research is motivated by the limited use of technology-based learning media in Social Science subjects at SMP Negeri 32 OKU, where instruction still relies on conventional textbooks. The abstract nature of Social Science topics, specifically